Talaqqi dalam Ilmu Qira’at : Studi Analisis Perbandingan Talaqqi Qira’at Di Indonesia dan Suriah (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study presents a comparative analysis of the practice of talaqqi in the science of qira’at in Indonesia and Syria, two significant regions in the transmission of sanad-based Qur’anic recitation. Based on the premise that talaqqi is the primary method for preserving the authenticity of the Qur’an—yet its standards, patterns, and scholarly framework have developed differently across regions this research aims to identify the similarities and differences in requirements, implementation methods, stages, and reference texts used in talaqqi qira’at in both countries. The study employs a descriptive qualitative approach with a multi-site design: in Indonesia at Pondok Pesantren Al-Munawwir Krapyak, Yanbu’ul Qur’an Kudus, Bustanu ‘Usysyaqil Qur’an Demak, and Al-Hikmah Semarang; and in Syria at Muhyiddin Ibn ‘Arabi Mosque, Mujamma’ Sheikh Ahmad Kuftaro, Maghribiyah Mosque, and the Qira’at Department of Bilad Syam University, Al-Fath al-Islamy branch. Data were obtained through in-depth interviews, observation, and document analysis, and then analyzed descriptively and analytically. The findings reveal that both countries require memorization of the Qur’an (30 juz), conduct talaqqi through face-to-face musyafahah, follow the sequential stages of ifrād jam‘ (including mufradat, jama‘ shughra, and jama‘ kubra), and refer to the Syāthibiyyah poem as a foundational text. However, Indonesia tends to focus on qira’at sab‘ah within the pesantren system, with simpler entry requirements and reliance on the practical manual Faidhul Barokat. In contrast, Syria emphasizes qira’at ‘asyrah with stricter selection standards, implementation in mosques and universities, recitations accompanied by evidence from Syāthibiyyah and ad-Durrah, and extensive support from various commentaries and jam‘ al-qirā’āt muṣḥafs. These findings reinforce the role of Indonesian pesantren in the global qira’at tradition and provide a basis for evaluating and developing a more integrative talaqqi qira’at curriculum that balances theoretical understanding and practical mastery.